Business Information Systems Workshops BIS 2011 International Workshops and BPSC International Conference, Poznan, Poland, June 15-17, 2011. Revised Papers - Abramowicz, Witold; Macaiaszek, Leszek; Węcel, Krzysztof; SpringeringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the three workshops that were organized in conjunction with the International Conference on Business Information Systems, BIS 2011, which took place in Pozna?, Poland, June 15-17, 2011.The 18 workshop papers presented were carefully reviewed and selected from 38 submissions. The topics covered are applications and economics of knowledge-based technologies (AKTB), business and IT alignment (BITA), and legal information systems (LIT). In addition, eight papers from the co-located Business Process and Services Computing Conference (BPSC) are also included in this volume.
Electronic reproduction.
Keywords: Economics; Information systems; Management information systems; Business -- Data processing -- Congresses; Management information systems -- Congresses; Information technology -- Congresses